Cholera Toxoid Boosts Serum Escherichia coli Antitoxin in Humans - Nalin, D. R. (1974)
Sera from individuals vaccinated with a cholera toxoid were tested to determine if sera with significant titers of cholera antitoxin could neutralize Escherichia coli thermolabile enterotoxin. Individuals who responded to immunization with significant increases in serum cholera antitoxin titers also showed increases in serum E. coli enterotoxin-neutralizing capacity. These findings suggested the possibility that the cholera toxoid vaccine may be useful in preventing disease caused by E. coli.